Warisan Ketara Seni Islam Tempatan: Mahkota Atap Masjid Tradisional Melaka - Ros Mahwati Ahmad Zakaria; Rabiah Abdul Rahman; Siti Nor Azhani Mohd Tohar (Malay Arts, Culture and Civilization Research Centre, Institute of the Malay World and Civilization, 2024)
Non-Indexed Publication